Renal Parenchyma Perforation and Hematoma Formation following Double-J Stent Insertion in a Solitary Functioning Kidney: An Unusual Complication. (2nd October 2012) - Nomikos, Michael S.; Chousianitis, Zacharias; Georgiou, Christos; Georgellis, Chrysostomos; Rikas, Panagiotis; Anagnostou, Theodoros
Abstract : Double-J ureteral stent insertion is a common urological procedure performed for the relief of ureteral obstruction or as a part of other endourological procedures. Several complications have been reported in the past. A case of a 62-year-old woman who was stented due to hydronephrosis of her solitary functioning left kidney and had renal perforation and retroperitoneal hematoma formation is presented. She was managed conservatively with blood transfusion and double-J stent repositioning in the collecting system the fifth postoperative day. Follow-up noncontrast computed tomography (CT) of the abdomen was performed the first and third months after stent placement which showed stabilization of the hematoma.